Declining Racial Stratification in Marriage Choices? Trends in Black/White Status Exchange in the United States, 1980 to 2010. Issue 1 (January 2017) - Torche, Florencia; Rich, Peter
The status exchange hypothesis suggests that partners in black/white marriages in the United States trade racial for educational status, indicating strong hierarchical barriers between racial groups. The authors examine trends in status exchange in black/white marriages and cohabitations between 1980 and 2010, a period during which these unions increased from 0.3 percent to 1.5 percent of all young couples. The authors find that status exchange between black men and white women did not decline among either marriages or cohabitations, even as interracial unions became more prevalent. The authors also distinguish two factors driving exchange: (1) the growing probability of marrying a white person as educational attainment increases for both blacks and whites (educational boundaries) and (2) a direct trade of race-by-education between partners (dyadic exchange). Although the theoretical interpretation of exchange has focused on the latter factor, the authors show that status exchange largely emerges from the former.